"Modelo de gestión para el control de los inventarios mediante la aplicación de la NIC 11 en la empresa Inmosolución S.A." - Montenegro Siguencia, Diana Fernanda (2013)
Important issues such as NICs, the difference between IAS 11 and IAS 2 phases of a construction project, and construction costs are covered. According to the knowledge of the company and the different concepts and use them as a basis for management model for inventory control, which are the main procedures, process control, flow charts and forms to be used as as the activity of building the application of IAS 11.